ED RAPID: A Novel Children's Hospital Direct Admission Process Utilizing the Emergency Department. Issue 2 (March 2020) - Louie, Jeffrey P.; Furnival, Ronald A.; Roback, Mark G.; Jacob, Abraham K.; Marmet, Jordan; Nerheim, Daniel; Hendrickson, Marissa A.
Abstract : Introduction: Direct hospital admission of children without evaluation in the emergency department (ED) is common, but few guidelines exist to maximize safety by assessing patient stability. This report describes a novel approach to support patient safety. Methods: An interdisciplinary children's hospital team developed a brief ED-based evaluation process called the ED Rapid Assessment of Patients Intended for Inpatient Disposition (ED RAPID). It entails a brief evaluation of vital signs and clinical stability by the ED attending physician and nurse. Children deemed stable are admitted to inpatient wards, whereas those requiring immediate intervention undergo full ED evaluation and disposition. We assessed outcomes for all children evaluated through this process from March 2013 through February 2015. Results: During the study period, we identified 715 patients undergoing ED RAPID evaluation. Of these, we directly admitted 691 (96.4%) to the hospital ward after ED RAPID evaluation; median ED treatment time was 4.0 minutes. We transitioned 24 (3.4%) to full ED evaluation, 14 (2.0%) because a ward bed was unavailable, and 10 (1.4%) for clinical reasons identified in the evaluation. We admitted four of the 10 stopped (40% of stops, 0.6% of total) to an intensive care unit, and 6 (60% of stops, 0.8% of total) to the hospital ward after ED care. Eight children (1.1%) admitted to the hospital ward after ED RAPID evaluation required a transfer to an intensive care unit within 12 hours. Conclusion: The ED RAPID evaluation process for children directly admitted to the hospital was feasible and effective in this setting. Abstract : Supplemental Digital Content is available in the text.